A rare but formidable complication of sepsis: symmetrical peripheral gangrene - Pandey, Prakash Chandra; Singh, Santosh Kumar; Ojha, Neelam (International Journal of Advances in Medicine, 2017)
Symmetrical peripheral gangrene (SPG) is a rare clinical entity. It was first described in late 19th century and since then has been reported with array of medical conditions mainly those complicated with shock, sepsis, and disseminated intravascular coagulation (DIC). Here in, we describe a patient with sepsis and SPG. Clinicians should be aware of this entity as early recognition can help in reducing morbidity and mortality.